Asoka V Waste Bank as a Pillar of Urban Environmental Empowerment: A SWOT Analysis of Waste Sorting in Makassar City - Ikram, Mulkhaeri; Mardiana, Wa Ode Sitti; Cabui, Cornelia Evelin; Weri, Firda; Bako, Seven Marganda; Ayu, Monica (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The waste problem in Makassar City is increasingly complex, especially due to the increasing volume of waste that accumulates at the Antang Final Disposal Site (TPA). This condition requires a more effective waste management strategy, one of which is through optimizing the role of the Waste Bank. This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT analysis) of the Asoka V Unit Waste Bank as one of the best waste banks in Makassar City. The research uses a descriptive qualitative method with data collection techniques through in-depth interviews, observations, and documentation. The results of the study show that the Asoka V Unit Waste Bank has strengths in the form of adequate facilities and continuous collaboration with private parties such as Pegadaian, while the weakness lies in the decline in the support of the village government. The opportunities are obtained from the support of the Environment Agency and increasing public awareness of waste management, while the threat comes from the increasing volume of waste and the lack of active participation of some residents. This research emphasizes that multistakeholder synergy is the key in strengthening the role of Waste Banks as an alternative solution in reducing the burden of waste at the Antang Landfill.